ANALISIS STRENGTHS DAN OPPORTUNITY DALAM PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH PADA KELOMPOK SUMBER MAKMUR DI DESA PAYUDAN DUNDANG - Ahmad Majdi Tsabit; Dana Rizki Akbar; Moh. Imron (Reinforce: Journal of Sharia Management, 2022)
Payudan Dundang Village has a lot of potential for Micro, Small and Medium Enterprises (MSMEs) which are sourced from agriculture and plantations. This study aims to analyze and to identify the problems faced and formulate strategies in the development of Micro Small and Medium Enterprises (MSMEs) in Payudan Dundang Village, as one of the leading sectors in helping improve the economy of the people of Payudan Dundang Village. This research used qualitative method through a process of observation, interviews, and documentation presented in the form of data, then the data analysis used SWOT matrix analysis to find out the strengths, weaknesses, opportunities and threats. The informants used as the data source consisted of the Leader of Group Sumber Makmur, member of grup Sumber Makmur, Payudan Dundang people. The research implementation time is one mount. The results of this study indicate that there are problems for every Micro, Small and Medium Enterprise (MSMEs) actor in Payudan Dundang Village such as: Product packaging, marketing, resources human, the introduction of technology, social and economy, so that the development of MSMEs in Payudan Dundang Village, has not been implemented properly. While the right strategy for developing MSMEs in Payudan Dundang Village Guluk- guluk district is the SO (Growth) Strategy. The SO (Growth) strategy is a strategy that utilizes existing strengths to increase its competitive advantage.